Relationship between Self Control and Smoking Behavior among Adolescents - Faturahman, Muhamad Rivaldi Nur (Jurnal Health Society, 2024)
Introduction: Adolescents become individuals who are easily influenced by the surrounding environment, so deviant behavior in the form of juvenile delinquency often occurs. One type of juvenile delinquency that dominates is smoking behavior. Smoking behavior can be influenced by various factors, namely factors from within and outside the individual. One of the personality factors associated with smoking behavior is self control. The purpose of this study was to determine the relationship between self control and smoking behavior in adolescents at SMKS PGRI 1 Sukabumi City. Method: This type of research is correlational with a cross sectional approach. The population and sample were all 10th grade male students at SMKS PGRI 1 Sukabumi City, namely 98 people using total sampling. Data analysis using Chi Square statistical test. Result: Based on the Chi Square statistical test results showed that the p-value was 0.000 (p-value <0.05) which means that there is a relationship between self control and smoking behavior in adolescents at SMKS PGRI 1 Sukabumi City. Conclusion: There is a relationship between self control and smoking behavior in adolescents at SMKS PGRI 1 Sukabumi City.